Development of nearpod-based interactive learning media for pancasila education bhineka tunggal ika - Yeni Aswita; Al Rafni; Hasrul Hasrul; Junaidi Indrawadi (Journal of Educational and Learning Studies, 2026)
This study aimed to develop and validate a Nearpod-based interactive learning medium for the Bhineka Tunggal Ika topic in Grade X Pancasila Education. A Research and Development (R&D) approach employing the ADDIE model was adopted. The product was validated by subject matter, language, and media experts and subsequently evaluated through one-to-one, small-group, and field trials involving Grade X students at SMAN 9 Muaro Jambi. Data were collected using observations, interviews, questionnaires, and learning achievement tests and analyzed descriptively using percentage-based feasibility criteria. The developed media achieved feasibility scores of 83% (content), 85% (language), and 88% (media). Practicality testing yielded positive responses, with scores of 92%, 95%, and 89%, while approximately 91% of students correctly completed the embedded assessments. The Nearpod-based learning media is valid, practical, and suitable for supporting interactive and student-centered learning in Pancasila Education